IMPEDIMENTE DE INTERACȚIONARE PRIN E-COMUNICARE A ENTITĂȚILOR DE DREPT PRIVAT CU INSTITUȚIILE ADMINISTRAȚIEI PUBLICE - Bordian, Mariana (CEP USM, 2022)
The achievement of economic goals by private law entities is in direct connection with the activity of public administration authorities. Thus, local and central government authorities are directly interested in creating facilities for the operation of private law entities and in removing any impediments, including communication, information and immediate release of permissive documents. In particular, changes in the ownership of immovable property by private law entities are made through various unnecessary and excessively bureaucratic steps
Keywords: e-comunicare